Behind the lenses: Biases in the contribution of wildlife photography to biodiversity representation - Héctor Ruiz‐Villar; Ana Morales‐González; Jon Morant (People and Nature)
Abstract Nature‐related visual media has a significant impact on today's society by engaging the public in conservation problems and promoting pro‐environmental behaviours. Although major attention has been paid to how some types of visual media (e.g. documentaries) offer unrealistic portrayals of the natural world, biases on representation by wildlife photography remain unexplored. In the present study, we assessed biases in wildlife photography at spatial, temporal, taxonomic, conservation status and selection criteria scales, and modelled the factors influencing the probability of portrayed organisms winning a wildlife photography contest by using data on 1333 pictures featured in the Wildlife Photographer of the Year, one of the most popular wildlife photography competitions worldwide. The representation of biomes mostly coincides with their extension on the planet. However, we detected an overrepresentation of temperate (broadleaf and conifer), Mediterranean and tropical forests. We detected a positive change over time in representing historically neglected taxa, such as insects. We also detected an increase in representation of Mangroves, Marine Ecosystems, Tundra and temperate forests and grasslands. Mammals and birds were overrepresented in photographs while insects and plants were underrepresented, and so were species listed as ‘Least Concern’ and ‘Data Deficiency’. The top 10 ranking species included charismatic carnivore species. Our results showed that the jury's choice offered a more diverse representation of biodiversity than the people's choice, and the winning photographs showcased fewer taxonomic groups than the non‐winning pictures. Realm, domain and colourfulness influenced the probability of an organism's picture being winner, but the variability explained by our model reflects that there are a large number of unexplored determinants (e.g. socio‐economical, technical or emotional). Our research detected a trend towards a more balanced representation of the natural world in wildlife photography, although biases are yet large, which may influence people's perception of the current status of species and habitats they encompass. Our results highlight a need to evenly represent species and ecosystems to increase public awareness, which requires providing data on species identity and conservation status to increase public knowledge. Finally, we underscore the need to report compliance with ethical guidelines when photographing wildlife. Read the free Plain Language Summary for this article on the Journal blog.